The Relationship between Self Efficacy and Resilience in New Psychology Students at University X - Aprilia Nanda Nabilah; Riza Noviana Khoirunnisa (Universitas Negeri Surabaya, 2023)
This study aims to determine the relationship between self-efficacy and resilience in new students majoring in Psychology at Surabaya State University using a correlational quantitative research method. The population in this study were 320 new psychology students with the criteria of being active psychology new students in college and taking their second semester. The subjects of this study were 134 new students who were determined by quota sampling technique. The instruments used in this research are the self-efficacy scale and the resilience scale. The data processing used is product moment correlation analysis with a significance level of 5%. Based on the analysis results obtained a correlation value of 0.610 and a significance value of 0.001 <0.05. This means that there is a positive relationship between self-efficacy and resilience in new Psychology students at Surabaya State University. Which if the self-efficacy of new students is high, then the level of resilience in new students will also be higher. Vice versa, if the self-efficacy of new students is low, then the level of resilience in new students will also decrease.